2009
DOI: 10.1007/s11240-009-9538-6
|View full text |Cite
|
Sign up to set email alerts
|

High frequency plant regeneration following abnormal shoot organogenesis in the medicinal tree Hovenia dulcis

Abstract: An efficient plant regeneration protocol for shoot organogenesis from Hovenia dulcis callus cultures was established. Induction of organogenic callus was achieved on Murashige and Skoog (MS) medium supplemented with 4.65 lM kinetin and 4.5 lM 2,4-dichlorophenoxyacetic acid (2,4-D). Further differentiation of organogenic callus into primordia, shoot-like structures, and plantlets was achieved on MS medium supplemented with 0.23 lM gibberellic acid (GA 3 ) and 0.46 lM kinetin. Numerous abnormal shoots developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…In the present study, friable calli were observed when 2,4-D and PIC were added to the culture medium, while only NAA induced compact callus which is in contrast with Jeong et al (2009) findings, where 2,4-D promoted the formation of compact callus in leaf explants. Similar results were reported for other species such as Gossypium hirsutum, where 2,4-D promoted only friable callus while NAA was responsible for compact callus formation (Baksha et al, 2006).…”
Section: Dpph Radical Scavenging Assaycontrasting
confidence: 99%
“…In the present study, friable calli were observed when 2,4-D and PIC were added to the culture medium, while only NAA induced compact callus which is in contrast with Jeong et al (2009) findings, where 2,4-D promoted the formation of compact callus in leaf explants. Similar results were reported for other species such as Gossypium hirsutum, where 2,4-D promoted only friable callus while NAA was responsible for compact callus formation (Baksha et al, 2006).…”
Section: Dpph Radical Scavenging Assaycontrasting
confidence: 99%
“…In the present investigation, it was observed that the total number of regenerants increased as the concentrations of TDZ increased in combination with 0.5 mg/L GA 3 or 0.25 mg/L NAA. This was in line with the observations on differentiation of organogenic callus into plantlets in Hovenia dulcis [33] on MS medium supplemented with 0.23 µM gibberellic acid and 0.46µM kinetin. Similarly maximum number of shoots was achieved from leaf section callus of Hyptis suaveolens [34] on MS medium containing 0.5 mg/L BA and 0.5 mg/L GA 3 .…”
Section: Discussionsupporting
confidence: 91%
“…Molecular marker techniques, such as random amplified polymorphic DNA (RAPD) analysis, have been used to assess variability or similarity within or between the plants derived from plant tissue culture and the donor plant (Jeong et al 2009;Jain et al 2011). RAPD is a simple, largely automatable technique which requires only a small amount of DNA and can be performed without the use of radioactivity (Williams et al 1990).…”
Section: Introductionmentioning
confidence: 99%